Dieckol, an Algae-Derived Phenolic Compound, Suppresses UVB-Induced Skin Damage in Human Dermal Fibroblasts and Its Underlying Mechanisms - Lei Wang; Jun-Geon Je; Hye-Won Yang; You-Jin Jeon; Seungheon Lee (MDPI AG, 2021)
Ultraviolet (UV) irradiation is considered to be the primary environmental factor that causes skin damage. In the present study, we investigated the protective effect of dieckol (DK), a compound isolated from the brown seaweed Ecklonia cava, against UVB-induced skin damage in human dermal fibroblasts (HDF cells). The results indicated that DK effectively inhibited the activity of collagenase. DK remarkably reduced the intracellular reactive oxygen species level and improved the viability of UVB-irradiated HDF cells. Besides, DK significantly and dose-dependently improved collagen synthesis and inhibited intracellular collagenase activity in UVB-irradiated HDF cells. In addition, DK markedly reduced the expression of proinflammatory cytokines and matrix metalloproteinases. Further analyses revealed that these processes were mediated through the regulation of nuclear factor kappa B, activator protein 1, and mitogen-activated protein kinase signaling pathways in the UVB-irradiated HDF cells. In conclusion, these results indicate that DK possesses strong in vitro photoprotective effects and therefore has the potential to be used as an ingredient in the cosmeceutical industry.